Multistage Power Amplifier In 180nm Cmos Technology With Integrated Passive Linearizer For IEEE 802.15 Application - Gunasegaran, Premmilaah (2018)
As wireless communication standard continues to evolve accommodating the demand of high data rate operation, the design of RF CMOS power amplifier (PA) becomes ever challenging. PAs are required to operate more efficiently while maintaining stringent linearity requirement. In this work, the low power linear multistage CMOS power amplifier for BLE application is designed and implemented.